Gate Leakage Current Reduction With Advancement of Graded Barrier AlGaN/GaN HEMT - Palash Das; Dhrubes Biswas (Журнал нано- та електронної фізики)
The gate leakage current reduction solution of AlGaN/GaN HEMT device issue has been addressed in this paper with compositional grading of AlGaN barrier layer. This work is also conjugated with the critical thickness limitation of heterostructure material growth. Hence, critical thickness calculation of AlGaN over GaN has been kept in special view. 1D Schrodinger and Poisson solver was used to calculate the 2DEG concentration and effective location to use it in the ATLAS device simulator for the predictions. The proposed Al0.50Ga0.50N/Al0.35Ga0.65N/Al0.20Ga0.80N/GaN HEMT structure exhibits the leakage current of the order of around 15 nA/mm at gate voltage of 1 V.